Work-Life Balance, Couple Satisfaction, and Father Involvement: A Cross-Cultural Study - Gaby Ersinta Parung; Nuno Ferreira (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
The goals of the study were to identify: (a) the differences in father involvement level between fathers in the United Kingdom and Asia; (b) the differences in father involvement between fathers within Asia (Indonesia and Hong Kong); and (c) the factor that contributed to father involvement the most: work-life balance or couple satisfaction. By using snowball sampling, 256 fathers (51 from the United Kingdom, 106 from Indonesia, and 99 from Hong Kong) participated in the study via an online survey that measured their level of involvement, couple satisfaction, and work-life balance. Results revealed a statistically significant difference in father involvement between fathers from Indonesia and Hong Kong (t = 6.307, p < .000, 95% = 16.286, 31.101), but not between fathers from the United Kingdom and Asia (t = - .487, p = .627, 95% = - 8.003, - 4.841). Couple satisfaction was directly correlated to father involvement and also acted as the mediating factor between work-life balance and father involvement meaning that father involvement was influenced by a larger system that was interconnected with wider society as well as the couple relationship.